SAĞLIK SEKTÖRÜ ÇALIŞANLARININ DEMOGRAFİK ÖZELLİKLERİNİN GİRİŞİMCİLİK ALGISINA ETKİSİ: AĞRI ELEŞKİRT DEVLET HASTANESİ ÖRNEĞİ - SAYLAN, BÜNYAMİN (Fırat Üniveristesi, 2020)
Bilim ve teknolojide yaşanan gelişmelerle birlikte toplumda önemi artan olgulardan biri de girişimciliktir. Sağlık hizmeti sunan kuruluşlar bazı özellikleri bakımından diğer işletmelerden ayrılsalar da, son yıllarda diğer işletmeler gibi kaliteli sağlık hizmetlerinin sunulmasının yanı sıra aynı zamanda pazarda rekabet ederek varlıklarını sürdürmeye de çalışmaktadırlar. Özellikle gelişmiş ülkelerde sağlık hizmeti sunan özel hastanelere yönelik kurumsal performans ölçümlerine dayanan akademik çalışmalara ve araştırmalara rastlamak mümkündür. Bu çalışmada da sağlık çalışanlarının girişimci kişilik özellikleri demografik özellikleri arasındaki ilişkiyi keşfedici ve doğrulayıcı analiz yöntemleriyle tespit etmek amaçlanmaktadır. Çalışmanın birinci bölümünde kavramsal çerçeve çizilmiştir. Bu bölümde kişilik, girişimci ve girişimcilik kavramları açıklanarak, girişimcilerin temel özellikleri ve temel işlevleri ve girişimcilik türleri incelenmiştir. İkinci bölümde girişimciliğin dünyada ve Türkiye'deki tarihsel gelişimi incelenmiş, girişimcilik sürecine ilişkin bilgiler açıklanmış ve girişimcilik kavramına yönelik ilgili çalışmaların yer aldığı literatür taramasına yer verilmiştir. Çalışmanın üçüncü ve son bölümünde Ağrı ili Eleşkirt İlçe Devlet Hastanesi çalışanlarının demografik özellikleri, girişimcilik algıları ve bunlar arasındaki ilişkiyi belirleyebilmek amacıyla alan araştırması yapılmıştır. Anahtar Kelimeler: Sağlık sektörü, sağlık çalışanı, girişimcilik, algı, demografik özellikler

Entrepreneurship is one of the increasingly important issues in society with the developments in science and technology. Although healthcare providers leave other businesses in terms of some features, they have been trying to survive by competing in the market as well as providing quality healthcare services like other businesses in recent years. It is possible to find academic studies and researches based on institutional performance measurements especially for private hospitals providing health care services in developed countries. In this study, it is aimed to identify the direct and indirect interactions between the entrepreneurial personality characteristics of the hospital managers and the institutional (financial and non-financial) performances of the hospitals through exploratory and confirmatory analysis methods and to develop models with confirmatory character based on these relationships. In the first part of the study, a conceptual framework is drawn. In this section, the concepts of personality, entrepreneurship and entrepreneurship are explained and the basic characteristics and basic functions of entrepreneurs and types of entrepreneurship are examined. In the second section, the historical development of entrepreneurship in the world and in Turkey is examined, information about the entrepreneurial process is explained and a literature review of related studies on the concept of entrepreneurship is given. In the third and final part of the study, field research was conducted to determine the demographic characteristics, entrepreneurial perceptions and the relationship between the employees of Eleşkirt District State Hospital in Ağrı province. Keywords: Health sector, health worker, entrepreneurship, perception, demographics
The impact of demographic characteristics of health sector workers on entrepreneurship perception: The case of Ağrı Eleşkirt State Hospital
Keywords: İşletme; Sağlık Kurumları Yönetimi